An in silico, structural, and biological analysis of lactoferrin of different mammals - da S. Vieira, Dielson [UNESP]; Polveiro, Richard C.; Butler, Thomas J.; Hackett, Timothy A.; Braga, Camila P.; Puniya, Bhanwar Lal; Teixeira, Weslen F.P.; de M. Padilha, Pedro [UNESP]; Adamec, Jiri; Feitosa, Francisco L.F. [UNESP] (Elsevier, 2021)
Lactoferrin (LF) belongs to the family of transferrins having multifunctional roles associated with the immune system of animals. To follow the aims for this study was selected 20 sequences of LF from mammalian species to evaluate the chemical, biological, and structural properties. Bioinformatics approaches used programs such as MAFFT for sequence alignment; PartitionFinder and MrBayes for phylogenetic approaches; I-TASSER, PROCHECK, Molecular Operating Environment (MOE), SWISS Model server, Peptide DB and Expasy ProtParam to estimate the physicochemical properties, to model the protein and predicted secondary structures. A phylogenic analysis shows species with genetic similarities clustered by complexity and unique grouping between Capra hircus, Macaca mulatta, and Myotis lucifugus, since they presented more amino acids but not overall changes in the iron-binding sites or biological aspects. Structural deviations in these clusters obtained in LF from those species were found in residues 46 (position 406-450), that is part of alpha-helix, and 37 (position 295-331), that is part of the beta-sheets. Our predicted model can be used to investigate more about structural aspects of LF and be applied for medicinal research.
Keywords: Globular glycoprotein; In silico; Lactotransferrin; Mammalians; Milk proteins